Efecto de tres densidades de siembra sobre el desempeño productivo del camarón gigante de malasia Macrobrachium rosenbergii cultivados en corrales - Lozano Del Aguila, Janina (2024)
The investigation was carried out in Yurimaguas, specifically at kilometer 24 of the road that takes Tarapoto, and took place during the months of February to April 2021. This sought to determine the impact of three different cultivation densities on the growth of the giant shrimp of Malaysia, Macrobrachium rosenbergii. To do this, an experimental design was established that included three different treatments: T1 with 5 PL/ m2 , T2 with 7 PL/ m2 and T3 PL/ m2 , each with three repetitions, resulting in a total of nine experimental units. Biometric measurements were carried out biometry. With the culmination of the study period, variance analysis and Tukey test were applied to identify significant differences between treatments. Additionally, the physicochemical conditions of water were monitored every fifteen days. It was determined that the growth of M. rosenbergii was influenced by planting density, being the T1 treatment that obtained better results in size and weight, evidencing a decrease in these parameters with the increase in culture density and a higher rate of Survival to the lower density. In conclusion, the physicochemical conditions of water remained constant in all cultivation units and within the appropriate parameters for the optimal shrimp development.